Teacher Creativity in Utilizing Technology as a Media for Islamic Religious Education Learning at SDN Pasirtaman - Euis Latipah; Salsabila Muthmainah; Siti Mulyanah; Syifa Nuriah (Penerbit Hellow Pustaka, 2025)
This study aims to explore the creativity of teachers in utilizing technology as a learning medium for Islamic Religious Education (PAI) at SDN Pasir Taman. The research was conducted using a qualitative descriptive method through observations, interviews, and documentation. The findings reveal that teachers at SDN Pasir Taman demonstrate high creativity in designing technology-based learning that suits the characteristics of elementary school students who tend to be easily distracted, enjoy hands-on activities, and exhibit high levels of classroom activity. Teachers use various digital tools such as educational videos, interactive presentations, learning applications, and virtual simulations to deliver PAI materials in ways that are more engaging and easier to understand. The use of technology is not limited to content delivery but is also integrated with active and participatory learning models. Moreover, teachers are able to overcome limitations in infrastructure by developing alternative media and utilizing offline resources creatively. This study highlights that teacher creativity in integrating technology is crucial in enhancing student motivation and comprehension, especially in subjects like religious education that require contextual and value-based understanding.